Nivolumab for metastatic uveal melanoma: a multicenter, retrospective study. Issue 5 (October 2021) - Tacar, Seher Yildiz; Selcukbiricik, Fatih; Yilmaz, Mesut; Erturk, Kayhan; Murat Sarici, Ahmet; Gulturk, Ilkay; Ayhan, Murat; Tural, Deniz
Abstract : Systemic treatment options with proven efficacy for the treatment of metastatic uveal melanoma are limited. In this study, we aimed to evaluate the efficacy of nivolumab in metastatic uveal melanoma patients. In our multi-center study, the files of patients who received nivolumab treatment with a diagnosis of metastatic uveal melanoma were retrospectively reviewed and their information was recorded. Seventeen patients were enrolledand 16 patients were evaluable for efficacy. The objective response rate (ORR) was 18% including one confirmed complete response and two confirmed partial responses. The median progression-free survival (PFS) was 5.8 months (95% CI, 0.03–11.57 months), and the median overall survival (OS) was 10.5 months (95% CI, 3.87–14.14 months). Significant longer OS and PFS were observed in patients with the performance status of the Eastern Cooperative Oncology Group (ECOG-PS) 0. Although significant longer OS was detected in patients with low median lactate dehydrogenase (LDH) levels, no significant difference was found in PFS. Grade 1 and 2 fatigue and decreased appetite were the most common side effects associated with treatment (17%); grade 3 and 4 side effects were not observed. Immunotherapy is also emerging as a treatment option among the limited number of treatment options in metastatic uveal melanoma (mUM), but its efficacy needs to be demonstrated with prospective studies involving a larger number of patients.